Anterior Shoulder Dislocation with Concomitant Fracture of processus coracoideus and tuberculum majus humeri - Case Report - Ševčík, M; Uhrin, T; Vidovič, D (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2022)
Glenohumeral joint is the most frequently dislocated joint of the human body. Concomitant fractures of the coracoid process and tuberculum majus in humeral dislocation of the shoulder joint are rarely described. Concomitant fractures are results of a significant contraction of the surrounding muscles and rotator cuff during a cerebral paroxysm. Due to the small number of cases, the treatment of such injuries is not simple and it is based on an algorithm for treatment of isolated injuries of these anatomical structures. In this case report, we describe a concomitant fracture of the coracoid process and tuberculum majus during an anterior shoulder dislocation in 25-year-old patient after an epileptic seizure. The injury was treated in our department surgically, with a good functional result. The absolute Constant score for the operated arm is 95 points, the relative Constant score is 97%, DASH score 0, VAS score 0.
Keywords: fraktury kostí; Shoulder Dislocation; processus coracoideus; Coracoid Process; Adult; dospělí; Humerus; Shoulder Joint; Humans; lidé; luxace ramenního kloubu; ramenní kloub; humerus; Fractures, Bone